2015
DOI: 10.1155/2015/979645
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Age and Latent Cytomegalovirus Infection on NK-Cell Phenotype and Exercise Responsiveness in Man

Abstract: The redeployment of NK-cells in response to an acute bout of exercise is thought to be an integral component of the “fight-or-flight” response, preparing the body for potential injury or infection. We showed previously that CMV seropositivity impairs the redeployment of NK-cells with exercise in the young. In the current study, we examined the effect of aging on the redeployment of NK-cells with exercise in the context of CMV. We show here that CMV blunts the exercise-induced redeployment of NK-cells in both y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 42 publications
(69 reference statements)
2
16
0
Order By: Relevance
“…This redeployment is stepwise and preferential in the sense that it involves NK-subsets exhibiting a high differentiation phenotype (KIR+/NKG2A– vs. medium-differentiated KIR+/NKG2A+ and low-differentiated KIR–/NKG2A+). Bigley and co-authors ( 72 ) were able to replicate this finding in a sample of 40 subjects (50–64 vs. 23–39 years) undergoing 30 min of cycling exercise at 80% of maximum power. Interestingly, the post-exercise response to CMV was similar between young and old individuals ( 72 ).…”
Section: Impact Of Acute Exercise On Immune Cellsmentioning
confidence: 80%
See 2 more Smart Citations
“…This redeployment is stepwise and preferential in the sense that it involves NK-subsets exhibiting a high differentiation phenotype (KIR+/NKG2A– vs. medium-differentiated KIR+/NKG2A+ and low-differentiated KIR–/NKG2A+). Bigley and co-authors ( 72 ) were able to replicate this finding in a sample of 40 subjects (50–64 vs. 23–39 years) undergoing 30 min of cycling exercise at 80% of maximum power. Interestingly, the post-exercise response to CMV was similar between young and old individuals ( 72 ).…”
Section: Impact Of Acute Exercise On Immune Cellsmentioning
confidence: 80%
“…Bigley and co-authors ( 72 ) were able to replicate this finding in a sample of 40 subjects (50–64 vs. 23–39 years) undergoing 30 min of cycling exercise at 80% of maximum power. Interestingly, the post-exercise response to CMV was similar between young and old individuals ( 72 ).…”
Section: Impact Of Acute Exercise On Immune Cellsmentioning
confidence: 80%
See 1 more Smart Citation
“…Thus, whereas different studies have shown an age-associated increased expression of KIR (20, 62) and a decreased expression of NKG2A (20), others have not found significant differences in the expression of KIR or NKG2A in the elderly (14, 17, 18, 30) or even a decreased expression of KIR (CD158a) in middle age donors if they are CMV-seropositive (63). The expression of another inhibitory receptor KLRG-1 is significantly reduced with aging (21) and with CMV seropositivity in the young individuals (63). …”
Section: Discussionmentioning
confidence: 95%
“…D -**significant difference ingress and egress between CD28 null and CD28 + CD8 + T ANG cells in older individuals (P < 0.05). (Simpson et al 2007;Turner et al 2010;Witard et al 2012), with age differences apparent for various subpopulations of T cells (Spielmann et al 2014;Bigley et al 2015;Ross et al 2018). In this study, we show that older adults mobilize T ANG cells to a lesser extent than younger adults, albeit not statistically significant, with younger individuals mobilizing over 29 more T ANG cells in response to the exercise stressor.…”
Section: Discussionmentioning
confidence: 52%